KONSEP AKHLAK DALAM KITAB TANBIHUL MUGHTARRIN KARYA IMAM AS-SYA’RONI DAN RELEVANSINYA DENGAN PENDIDIKAN - Besari, Ahiel Ahdi; Yasin, Hadi; Kohari, Khalis (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
The modern era is an era where there is a lot of development, be it cultural development, educational development or technology. Indonesian society still upholds manners in relationships as children behave to their elders and relationships between friends. But along with the pace of development of the times and rapid changes in information technology have changed most of the world's people, especially teenagers. To get or achieve good morals in accordance with religious guidance, everyone must go through a process called the process of moral education. The concept related to moral education in Islam is contained in one of the books entitled Tanbihul Mughtarrin. Starting from the above background, the author formulates the problem as follows: How is the concept of morals in the book of Tanbihul Mughtarrin by Imam Ash-Shafi'roni? and How is the relevance of the book of Tanbihul Mughtarrin to education? The type of research that the author uses is library research, namely: The research collected data and information using the book of Tanbihul Mughtarrin by Imam Ash-Shafi'roni, the translation of Tanbihul Mughtarrin, the book of morals (the characteristics of a perfect human being), as well as journals and scientific works from other figures directly related to the discussion in this study. Data analysis in this research is carried out using descriptive analysis, which is research with work steps to describe an object, phenomenon, social setting, and the target of the research is answered in narrative writing. This means that the data and facts that have been collected by qualitative researchers are in the form of words or pictures. After that, to get a conclusion, the author uses an inductive reasoning pattern, which is a pattern of thought that departs from a specific thought and then draws general generalizations. The essence of the concept of morality in the book of Tanbihul Mughtarrin by Imam Ash-Shafi'roni and its relevance to education. The book of Tanbihul Mughtarrin contains an invitation to get closer to Allah SWT, reviewing the noble ethics of the righteous salaf scholars, by quoting their maqolah-maqolah and also quoting the words of previous Prophets related to noble ethics. And in its relevance to moral education is everything and the position of morals above education, even the Prophet Muhammad was sent to perfect morals.